2007
DOI: 10.1063/1.2803774
|View full text |Cite
|
Sign up to set email alerts
|

Scanning optical homodyne detection of high-frequency picoscale resonances in cantilever and tuning fork sensors

Abstract: Higher harmonic modes in nanoscale silicon cantilevers and microscale quartz tuning forks are detected and characterized using a custom scanning optical homodyne interferometer. Capable of both mass and force sensing, these resonators exhibit high-frequency harmonic motion content with picometer-scale amplitudes detected in a 2.5 MHz bandwidth, driven by ambient thermal radiation. Quartz tuning forks additionally display both in-plane and out-of-plane harmonics. The first six electronically detected resonances… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…The simplest way to meet the T 2 ≫ T condition is to use a mechanical oscillator with a higher resonance frequency. Alternatively, as demonstrated in this work, a higher mechanical mode of the tuning fork can be employed 45 . High-frequency detection has the added advantage that the interval between π -pulses (given by 1/(2 f TF )) becomes very short, which makes dynamical decoupling more efficient and in turn leads to improved sensitivity 42 , 46 .…”
Section: Resultsmentioning
confidence: 99%
“…The simplest way to meet the T 2 ≫ T condition is to use a mechanical oscillator with a higher resonance frequency. Alternatively, as demonstrated in this work, a higher mechanical mode of the tuning fork can be employed 45 . High-frequency detection has the added advantage that the interval between π -pulses (given by 1/(2 f TF )) becomes very short, which makes dynamical decoupling more efficient and in turn leads to improved sensitivity 42 , 46 .…”
Section: Resultsmentioning
confidence: 99%
“…To fully understand and quantitatively demonstrate the position-dependent nature of the multimode resonance spectra, we now focus on measuring the peak amplitude of each of the five resonance modes, while scanning the laser spot throughout the device area (that is, the so-called scanning spectromicroscopy) 33,34 . The left panels in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Detection using high-harmonic frequencies Atomic force microscope (AFM) with the microcantilever as central nowadays is becoming a conventional device in the detection of micro to nano-objects that helps to reveal the physical and chemical properties in nanoscale. [1][2][3][4][5] Several studies have been adopted to enhance the functionality of the cantilever via changing its cross-section materials [6][7][8][9][10] and dimensions [11][12][13][14][15] and revealed that the sensitivity of the cantilever sensor could be enhanced if higher modes of oscillation are used [16][17][18][19] and the quality factor could be increased, especially when functioned in liquids. 20,21) This is explained by the fact that the surface-to-bulk ratio is lower at higher-order modes, which leads to lower air/fluid damping.…”
mentioning
confidence: 99%